Possible mechanisms for intravenous immunoglobulin–associated hemolysis: clues obtained from review of clinical case reports. Issue 2 (14th July 2015) - Padmore, Ruth
<x xml:space="preserve">Abstract</x> BACKGROUND Intravenous immunoglobulin (IVIG) is an efficacious treatment modality for a number of conditions and is usually well tolerated with few reports of serious adverse events; however, the administration of IVIG may occasionally result in clinically significant hemolysis. STUDY DESIGN AND METHODS The literature was reviewed for case reports and case series of IVIG‐associated hemolysis. The cases were scrutinized for clues as to the possible mechanism(s) of the hemolysis. RESULTS Review of the 129 individual cases reported in the literature identifies clinical features shared by the majority of patients. These features included non‐O blood group patients and treatment with high‐dose IVIG as an immune‐modulating agent for an underlying inflammatory or immune‐mediated disorder. Other patient factors such as secretor phenotype, soluble ABH substance, and Fcgamma receptor polymorphisms may also play a role. CONCLUSIONS It is known that high‐dose IVIG given to non‐O blood group patients with underlying inflammatory and/or immune‐mediated disorders is associated with increased risk of hemolysis. This review reveals additional patient characteristics in cases of IVIG‐associated hemolysis, including underrepresentation of D– and group B cases, higher incidence in pediatric Kawasaki disease and unique at‐risk patient groups including allogeneic stem cell transplant recipients with group A donor in a group O recipient, and patients in whom soluble AB substance is removed by plasma exchange at the same time as receiving IVIG.